Combined water desalination and electricity generation through a humidification-dehumidification process integrated with photovoltaic-thermal modules: Design, performance analysis and techno-economic assessment. (January 2019) - Gabrielli, Paolo; Gazzani, Matteo; Novati, Nicolò; Sutter, Lara; Simonetti, Riccardo; Molinaroli, Luca; Manzolini, Giampaolo; Mazzotti, Marco
Graphical abstract: Highlights: Impact of system design, PVT configurations and HDH size, on system performance. Feasible and optimal operating regions as function of ambient conditions. Cost-optimal solar technology as function of electricity price and ambient conditions. Impact of water production, electricity price and HDH size on cost of clean water. Abstract: Humidification-dehumidification (HDH) processes have proved to be a promising solution for small-scale desalination, appropriate for water production in off-grid locations where the water demand does not justify the installation of conventional large-scale systems. With this contribution, we investigate the design and operation of an HDH process coupled with photovoltaic-thermal (PVT) solar modules for the simultaneous generation of clean water and electricity. The HDH system consists of established technologies, namely a humidification column and a heat exchanger, and is simulated through a commercial software accounting for heat and mass transfer limitations. On the other hand, PVT modules are a relatively new technology and their performance is determined experimentally to characterize the simultaneous generation of electricity and heat under realistic operating conditions. Based on the maximum-efficiency ratio of water to air mass flow rates, the optimal design of the system is determined for a wide range of ambient conditions by evaluating the impact of saline water flow rate, PVT configuration and HDH size on the amount of clean water produced. Then, the optimal operation of the system is characterized as function of the ambient conditions for a fixed system design. The state of the system is represented by the maximum process temperature, at the outlet of the PVT modules, whereas the performance is evaluated in terms of clean water and electricity generation. Finally, a techno-economic assessment is carried out to compare the proposed technology against conventional solar-driven HDH units, which use thermal and photovoltaic panels, for a wide range of electricity price, ambient conditions, amount of yearly water produced and size of the HDH process.